2015
DOI: 10.1097/dss.0000000000000385
|View full text |Cite
|
Sign up to set email alerts
|

Use of Photodynamic Therapy and Sterile Water to Target Adipose Tissue

Abstract: Verteporfin decreased adipose tissue after treatment. Sterile water injection had a statistically significant effect on adipose tissue histologically but did not substantially decrease the adipose tissue by ultrasound 4 to 6 weeks after intervention. Longer follow-up may be needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…When the body weight of the mice increased by 70% with HFD (HFD containing 60% fat) in 10 weeks, we randomly assigned them to four groups: vehicle-treated HFD only; high-fat diet with Ce6, 2.5 mg/kg, and light of a high fluence rate (HC2.5Hi); high-fat diet with Ce6, 5 mg/kg, and light of a low fluence rate (HC5Lo); and high-fat diet with Ce6, 5 mg/kg, and light of a high fluence rate (HC5Hi) ( Table 3 ). The mice were then administered an oral dose of Ce6 (2.5 or 5 mg/kg), and 3 h [ 29 ] later, PDT was performed using a 660 nm laser irradiation (2.56 mW/cm 2 and 4.96 mW/cm 2 ), while vehicle-treated HFD mice were administered with normal saline. PDT was repeated every 2 days for up to 4 weeks.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…When the body weight of the mice increased by 70% with HFD (HFD containing 60% fat) in 10 weeks, we randomly assigned them to four groups: vehicle-treated HFD only; high-fat diet with Ce6, 2.5 mg/kg, and light of a high fluence rate (HC2.5Hi); high-fat diet with Ce6, 5 mg/kg, and light of a low fluence rate (HC5Lo); and high-fat diet with Ce6, 5 mg/kg, and light of a high fluence rate (HC5Hi) ( Table 3 ). The mice were then administered an oral dose of Ce6 (2.5 or 5 mg/kg), and 3 h [ 29 ] later, PDT was performed using a 660 nm laser irradiation (2.56 mW/cm 2 and 4.96 mW/cm 2 ), while vehicle-treated HFD mice were administered with normal saline. PDT was repeated every 2 days for up to 4 weeks.…”
Section: Resultsmentioning
confidence: 99%
“…Obesity is considered an epidemic that is rapidly spreading across the globe and causing a variety of metabolic diseases [ 1 ]. In recent years, PDT has become an alternative choice for individuals to reduce their weight amidst the hustle of life, besides various therapeutic treatments for obesity and its related metabolic disorders [ 26 , 27 , 28 , 29 , 30 ]. For the first time, the two different murine models of obesity investigated the pharmacokinetic properties and ADME studies as well as evaluated the anti-obesity effects of Ce6-PDT by using PDT chamber systems.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Photodynamic therapy (PDT) is a therapeutic method used to treat tumors as well as some skin diseases, such as psoriasis and acne, by means of photosensitizers that enter the body and are activated by light of appropriate wavelengths, resulting in a series of photochemical toxic effects, i.e., the generation of singlet oxygen ( 1 O 2 ) and other reactive oxygen species (ROS) that bind to the corresponding target tissues, leading to tissue damage and cell death. Local PDT mediated by verteporfin or indocyanine green was previously reported to reduce fat [ 129 ]. PDT acts directly and rapidly but is only applicable to superficial fat due to the limitation of light penetration.…”
Section: Biomaterial-assisted Anti-obesity Therapymentioning
confidence: 99%
“…It has been reported that PDT mediated by photosensitizers (PSs) can reduce fats since reactive oxygen species (ROS) produced by PSs could rapidly drive adipocyte death upon laser illumination. [11][12][13][14][15] In the meantime, the other strategy for obesity treatment is adipose browning induction, which could transform white adipose tissue (WAT) into thermogenic adipose tissue. [16,17] WAT exists in excess energy in the form of triacylglycerol (TAG), while thermogenic adipose tissue dissipates energy as heat.…”
Section: Introductionmentioning
confidence: 99%